Metodologia para a implantação de PARQUELABS: o caso do Parque Tecnológico de Uberaba - RESENDE, Raquel Mendonça do Vale (2016)
The process of interaction between the elements of the Triple Helix: Government, academia and business, is still lacking in Brazil and worldwide. As an alternative to optimize this relationship, the Technology Parks has become known for providing in appropriate physical spaces, installation of technology-based developments close to universities and research centers. This paper aims to set up a methodology for the implementation of this interaction promoters spaces in coworking format, entitled Parquelabs. The spaces created are aimed addition to hosting the academic community interested in developing their projects or startups, of increasing the connection and the visibility of the Technology Park in the city of Uberaba, in the places of their implementation, accelerating its consolidation. The proposed methodology has a protocol which starts from the choice of suitable sites for the implementation of spaces, involves the physical structure of the respective locations, and involves decisions related to governance, activities and risk management, with planning and systematic monitoring. It involves the management teams of the Park and the chosen entities. This methodology sets these innovation habitats as birthplaces of technology and innovative based companies, from the knowledge generated in educational institutions and local research. The coworkings for development of startups, installed on the main local academic communities, solve a problem which was soon detected in the first months of work with the management of the Technological Park of Uberaba, which was some distance from the teaching and research entities, the activities of the Technology Park, which urgently needed to be restored, as the Certi Foundation reports showed. As a result of the application of the methodology, the city will rely on a number of spaces for development activities involving the entire local ecosystem of innovation, stimulating innovative entrepreneurship environment in the city and the region. The perspective is that this methodology will contribute as an alternative to foster the creation of innovative new products and services, generating economic and technological development to society.